Organization of a Wireless System for Individual Biomedical Data Collection - Yeroshenko, O.; Prasol, I.; Trubitsyn, O.; Rebezyuk, L. (My University, 2020)
The article discusses the organization of a wireless system for collecting biomedical information, which is intended to everyday control the basic human life parameters. The system is based on a wireless sensor system and allows the data transfer to mobile devices or a computer for further processing/
Keywords: ZigBee; transmission speed; biomedical parameters; topology; Wi-Fi; Bluetooth